The Influence of Motivation and Perception on the Intention to use and its Impact on the Decision (Installation) of PLN Applications Mobile - Pamungkas, Ikhsanurrahman; Rivai, Alimuddin Rizal (Dinasti Publisher, 2025)
The gap between the number of registered users and active users of the PLN Mobile application indicates a suboptimal adoption of digital services. This study aims to analyze the influence of customer motivation and perception on the intention to use, and its impact on the decision to install the PLN Mobile application among non-user customers in the PLN UID Banten area. This research employed a quantitative approach using a cross-sectional survey method and purposive sampling technique involving 100 respondents. Primary data were collected through a Likert-scale questionnaire (ranging from 1 to 7) and analyzed using multiple linear regression and Sobel test. The findings reveal that motivation does not have a significant influence on either the intention to use or the decision to install the application. In contrast, customer perception significantly affects both the intention and the decision to use the application. Furthermore, the intention to use is proven to act as a mediating variable in the relationship between motivation and perception with the decision to use. These findings indicate that PLN should focus its strategies on enhancing perceived quality and user experience to promote broader adoption of the application.